TRANSFORMASI SPRITUAL: ( DARI TAKHALLI, TAHALLI KE TAJALLI ) - Muspian Muspian (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Spiritual transformation in Sufism is a process of purification and inner enlightenment that guides humans toward true closeness with Allah. In the Sufi perspective, human beings are not merely physical and intellectual entities; they also possess a spiritual dimension that forms the core of their existence. This process unfolds through three essential stages: takhalli (cleansing the self from blameworthy traits), tahalli (adorning the self with noble character), and tajalli (the manifestation of divine light in the heart). These stages are not merely theoretical constructs but serve as a spiritual roadmap, especially relevant in addressing the existential and moral crises of the modern age. In a fast-paced, materialistic world, spiritual transformation offers a vital path to achieving inner balance and social harmony. Through this process, Sufism not only strengthens an individual's spiritual integrity but also contributes to the formation of a more compassionate and ethical society. Therefore, spiritual transformation through takhalli, tahalli, and tajalli becomes the key to attaining purity of the soul, gnosis of God, and a more meaningful life amidst contemporary challenges.